"I did not intend to stop. I just could not stand cigarettes any more." A qualitative interview study of smoking cessation among the elderly - Rudebeck Carl; Melbye Hasse; Medbø Astri (BMC Family Practice, 2011)
Abstract Background Every year, more than 650,000 Europeans die because they smoke. Smoking is considered to be the single most preventable factor influencing health. General practitioners (GP) are encouraged to advise on smoking cessation at all suitable consultations. Unsolicited advice from GPs results in one of 40-60 smokers stopping smoking. Smoking cessation advice has traditionally been given on an individual basis. Our aim was to gain insights that may help general practitioners understand why people smoke, and why smokers stop and then remain quitting and, from this, to find fruitful approaches to the dialogue about stopping smoking. Methods Interviews with 18 elderly smokers and ex-smokers about their smoking and decisions to smoke or quit were analysed with qualitative content analysis across narratives. A narrative perspective was applied. Results Six stages in the smoking story emerged, from the start of smoking, where friends had a huge influence, until maintenance of the possible cessation. The informants were influenced by "all the others" at all stages. Spouses had vital influence in stopping, relapses and continued smoking. The majority of quitters had stopped by themselves without medication, and had kept the tobacco handy for 3-6 months. Often smoking cessation seemed to happen unplanned, though sometimes it was planned. With an increasingly negative social attitude towards smoking, the informants became more aware of the risks of smoking. Conclusion "All the others" is a clue in the smoking story. For smoking cessation, it is essential to be aware of the influence of friends and family members, especially a spouse. People may stop smoking unplanned, even when motivation is not obvious. Information from the community and from doctors on the negative aspects of smoking should continue. Eliciting life-long smoking narratives may open up for a fruitful dialogue, as well as prompting reflection about smoking and adding to the motivation to stop.